MAKNA KATA UFF DALAM AL-QUR’AN - Riana Ulfa; Andy Hariyono (Al-Dirayah, 2022)
This study is motivated by the distance of the values ​​of the Koran in modern life which is increasingly sophisticated which has shifted moral values ​​and has an impact on various moral deviations in everyday life. One of them is the behavior of children towards their parents. Like disobedient and dutiful to his parents. The main problems in this study are: 1. What is the meaning of the word uff in the Quran? This type of research is library research, by collecting data or materials related to the discussion and problems, which are taken from library sources in the form of books, encyclopedias, dictionaries, journals, documents and so on. Then analyzed using the tahlili method, namely the author wants to know how the Qur'an can play a role in life, especially in ethics to parents by analyzing the interpretation of surah al-Isra' verse 23, al-Anbiya' verse 67 and al-Ahqaf verse 17, and in that verse there is the word uff which means ah and the explanation will be taken from several commentaries. The results of this study indicate that: 1. the meaning of the word uff in the Qur'an is a word or action that contains the meaning of irritation, boredom, or other bad attitudes that show disrespect and the results can hurt the hearts of both parents.